2004
DOI: 10.1530/rep.1.00020
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and the neoplastic process

Abstract: Endometriosis is a frequent disorder that commonly presents with infertility and pelvic pain. Although the precise aetiology of endometriosis is unclear, it is generally considered to involve multiple genetic, environmental, immunological, angiogenic and endocrine processes. Genetic factors have been implicated in endometriosis but the susceptibility genes remain largely unknown. Although endometriosis is a benign disorder, recent studies of endometriosis suggest endometriosis could be viewed as a neoplastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
149
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 99 publications
5
149
0
5
Order By: Relevance
“…The effectiveness of those treatments in vitro and in animal models relies on the modulation of cellular mechanisms responsible for invasion, unrestrained growth, neoangiogenesis, and distant spreading of endometriotic cells. 12 In line with those observations, it has recently been shown that ovarian endometriotic cells display a high endogenous oxidative stress, with profound alteration of the reactive oxygen species (ROS) detoxification pathways associated with increased cellular proliferation and activation of the MAP kinase ERK 1/2 pathway. 10 Activation of the ERK pathway has been found in eutopic endometrium and in ovarian endometrioma of a large number of women with ovarian endometriosis.…”
mentioning
confidence: 73%
“…The effectiveness of those treatments in vitro and in animal models relies on the modulation of cellular mechanisms responsible for invasion, unrestrained growth, neoangiogenesis, and distant spreading of endometriotic cells. 12 In line with those observations, it has recently been shown that ovarian endometriotic cells display a high endogenous oxidative stress, with profound alteration of the reactive oxygen species (ROS) detoxification pathways associated with increased cellular proliferation and activation of the MAP kinase ERK 1/2 pathway. 10 Activation of the ERK pathway has been found in eutopic endometrium and in ovarian endometrioma of a large number of women with ovarian endometriosis.…”
mentioning
confidence: 73%
“…17 Endometriosis may show unrestrained growth and increased vascularization, and even features classically associated with malignancy, such as tissue invasion and metastasis. By detecting LOH in endometriosis lesions, we have also provided molecular evidence to suggest that endometriosis lesions can be true neoplasms, that is, they derive from a clonal proliferation of cells arising from genetic changes, which provide that clone with a replicative advantage.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, despite the histological and epidemiological evidence linking these two diseases, it is still unclear whether endometriosis is a precursor to EAOCs, or whether there is an indirect link involving common environmental, immunological, hormonal or genetic factors. 17 Molecular genetic studies of allele loss have been used to demonstrate clonal progression from precursor lesion to cancer. [18][19][20] In order to search for evidence of clonal progression from endometriosis to cancer, we analyzed 10 EAOC cases with coexisting endometriosis for common molecular genetic alterations in both the tumor and corresponding endometriosis, using 82 microsatellite markers spanning the genome.…”
mentioning
confidence: 99%
“…1 Based on the Swedish hospital data base, a large Swedish study involved 20 686 women who had a hospital discharge diagnosis of endometriosis. 17 This group reports a relative risk of 4.2 for ovarian cancer in women followed up for more than ten years after diagnosis of ovarian endometriosis.…”
Section: Gynaecological Cancermentioning
confidence: 99%
“…Myometrial invasion by endometrial glands, called adenomyosis, was previously recognised as a separate disease, but it frequently co-exists and shares etiological factors with extrauterine endometriosis. 1 Interestingly, most patients have a single form of the disease rather than a field effect.…”
Section: Introductionmentioning
confidence: 99%